"Art" in Slovak Cinemas from the Separation of the Slovak Republic to the Present Day - Križková, Eva (Iluminace, 2014)
The topic and content of the dissertation "Art" in Slovak cinemas from the independence of the Slovak Republic to the present.
Keywords: dissertation; Slovak cinema; art film